Iatrogenic oesophageal perforation during placement of an endoscopic vacuum therapy device - Halliday, Edwin (J Surg Case Rep, 2016)
Endoscopic vacuum-assisted closure (VAC) is increasingly being used as a means of managing perforations or anastomotic leaks of the upper gastrointestinal (GI) tract. Published outcomes are favourable, with few mentions of complications or morbidity. We present a case in which the management of a gastric perforation with endoscopic vacuum therapy was complicated by cervical oesophageal perforation. The case highlights the risks of such endoscopic therapeutic procedures and is the first report in the literature to describe significant visceral injury during placement of a VAC device for upper GI perforation. Iatrogenic oesophageal perforation is an inherent risk to upper GI endoscopy and the risk increases in therapeutic endoscopic procedures. Complications may be reduced by management under a multidisciplinary team in a centre with specialist upper GI services. There is no doubt that the endoscopic VAC approach is becoming established practice, and training in its use must reflect its increasingly widespread adoption.